Answer:
![(-11)/(4(x+3))+(1)/(12(x-1))+(8)/(3(x+2))](https://img.qammunity.org/2021/formulas/mathematics/college/qitbsj7d2vdf3t20hcye8o8hmz3tdix0y8.png)
Explanation:
![(3x - 2)/((x + 3)(x - 1)(x + 2))=(A)/(x+3)+(B)/(x-1)+(C)/(x+2)\\\\A=(3(-3)-2)/((-3-1)(-3+2))=(-11)/(4)\\\\B=(3(1)-2)/((1+3)(1+2))=(1)/(12)\\\\C=(3(-2)-2)/((-2+3)(-2-1))=(-8)/(-3)=(8)/(3)\\\\(3x - 2)/((x + 3)(x - 1)(x + 2))=\boxed{(-11)/(4(x+3))+(1)/(12(x-1))+(8)/(3(x+2))}](https://img.qammunity.org/2021/formulas/mathematics/college/bavxpleiueqbpvna5jaab0gjy2j08bets4.png)
__
When the denominator factors are linear and to the first degree, the corresponding coefficient can be found by eliminating that factor and evaluating the expression for the value of x that would make the factor zero.
As we showed above, the coefficient A is found by evaluating the expression for x=-3 (the zero of the denominator of A) with that factor eliminated from the denominator. Likewise for the others.